2011
DOI: 10.1002/btpr.585
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic generation of Mn(III)‐chelate as a chemical oxidant of different environmental contaminants

Abstract: The objective of this study was to investigate the enzymatic generation of the Mn(3+) -malonate complex and its application to the process of oxidizing several organic compounds. The experimental set-up consisted of an enzymatic reactor coupled to an ultrafiltration membrane, providing continuous generation of Mn(3+) -malonate from a reaction medium containing versatile peroxidase (an enzyme produced by Bjerkandera adusta strain BOS55), H(2) O(2) , MnSO(4,) and malonate. The effluent of the enzymatic reactor w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
1
4
1
Order By: Relevance
“…The maximum concentration in the enzymatic reactor was 616±42 μM, 1.5-fold higher than the value previously reported [25], probably due to the higher rates of Mn 2+ feeding (1.5 and 1.0 μM h −1 , respectively). According to this value, the maximum efficiency of conversion of Mn 2+ to Mn 3+ was 49 %, which is in agreement with previous findings where the conversion efficiency was around 42 % [22].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The maximum concentration in the enzymatic reactor was 616±42 μM, 1.5-fold higher than the value previously reported [25], probably due to the higher rates of Mn 2+ feeding (1.5 and 1.0 μM h −1 , respectively). According to this value, the maximum efficiency of conversion of Mn 2+ to Mn 3+ was 49 %, which is in agreement with previous findings where the conversion efficiency was around 42 % [22].…”
Section: Resultssupporting
confidence: 93%
“…Due to the high removal efficiencies observed in both experiments, these results suggested that at very low concentrations of NP (e.g., 454 nM), the reactor capacity is used only partially and probably the Mn 3+ -complex feeding rate was exceeding that required to achieve the oxidation of NP. Taboada-Puig et al observed that the higher the initial concentration of the Mn 3+ complex, the higher the percentage of the batch oxidation of the synthetic dye Orange II [22]; however, they evaluated molar ratios considerably lower than those studied in the present work (maximum molar ratio of 2.6).…”
Section: Resultscontrasting
confidence: 73%
See 2 more Smart Citations
“…The heterologous expression of VP in Aspergillus nidulans confirmed the ability of VP to oxidize Mn(II), and different aromatic compounds in the absence of manganese (RuizDueñas et al 1999b). The enzymatic generation of Mn(III) by VP for the oxidation ex situ of different pollutants has been proved (Taboada-Puig et al 2011). In addition, this enzyme has a long-range electron transfer (LRET) pathway similar to that shown in lignin peroxidase (LiP) (Johjima et al 1999;Blodig et al 1999;Ruiz-Dueñas et al 2009).…”
Section: Introductionmentioning
confidence: 99%